Effects of Sequence and Expression of Eight Anthocyanin Biosynthesis Genes on Floral Coloration in Four Dendrobium Hybrids - Nattaphan Kriangphan; Supachai Vuttipongchaikij; Chokchai Kittiwongwattana; Anongpat Suttangkakul; Phitsanu Pinmanee; Arpakorn Sakulsathaporn; Rawat Suwimon; Saowanee Suputtitada; Yindee Chanvivattana; Somsak Apisitwanich (My University, 2015)
Understanding the control of anthocyanin biosynthesis is beneficial to genetic improvement for floral production in Dendrobium orchids. Full-length cDNA of CHS, CHI1, CHI2, F3H, DFR, ANS, F3'5'H, and FLS was isolated from Dendrobium hybrids with purple, peach, white and greenish white flowers. Analysis of the deduced amino acid sequences and gene expression levels of the eight genes suggested potential causes of color variation among the hybrids. Peach hybrid (SC) was likely due to changes in anthocyanin production from cyanidin to pelargonidin through mutations in F3'H, and the low color intensity was likely derived from the low expression levels of CHI1 and CHI2. In addition, white hybrid (RW) was likely caused by several mutations in F3H and/or high expression levels of FLS, an enzyme that converts color flavonoid intermediates into colorless flavonols. Simultaneous loss of F3H, DFR, and ANS expression observed in another white hybrid (JW) indicated that an alteration of anthocyanin regulatory controls was likely the cause of white coloration. Furthermore, analysis of hybrid mutants bearing pale and dark flowers demonstrated the influence of the expression of anthocyanin genes on the intensity of flower colors. Data obtained from this work could contribute to new strategies for future orchid breeding.
Keywords: Dendrobium; White (mutation); Pelargonidin; Flavonols; Plant Gene Expression Analysis